2019
DOI: 10.1038/s41586-019-1767-1
|View full text |Cite
|
Sign up to set email alerts
|

Generation of stable heading representations in diverse visual scenes

Abstract: Many animals rely on an internal heading representation when navigating in varied environments [1][2][3][4][5][6][7][8][9][10] . How this representation is linked to the sensory cues defining different surroundings is unclear. In the fly brain, heading is represented by 'compass neurons' that innervate a ring-shaped structure, the ellipsoid body 3,11,12 . Each compass neuron receives inputs from visual-feature-selective 'ring neurons' [13][14][15][16] , providing the ideal substrate for the extraction of direc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
296
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(311 citation statements)
references
References 62 publications
14
296
1
Order By: Relevance
“…Instead, insects tended to briefly visit the perimeter and venture to the center in all the symmetrical arenas. Therefore, our results may be considered supporting evidence for the presence of an internalized representation of space in insects (Giurfa & Capaldi, 1999;Gould, 1986;Menzel et al, 2005;Webb, 2019;Wray, Klein, Mattila, & Seeley, 2008), especially taking into account that neural circuits for the processing of direction were recently discovered (Fisher, Lu, Alessandro, & Wilson, 2019;Kim, Hermundstad, Romani, Abbott, & Jayaraman, 2019).…”
Section: Discussionsupporting
confidence: 76%
“…Instead, insects tended to briefly visit the perimeter and venture to the center in all the symmetrical arenas. Therefore, our results may be considered supporting evidence for the presence of an internalized representation of space in insects (Giurfa & Capaldi, 1999;Gould, 1986;Menzel et al, 2005;Webb, 2019;Wray, Klein, Mattila, & Seeley, 2008), especially taking into account that neural circuits for the processing of direction were recently discovered (Fisher, Lu, Alessandro, & Wilson, 2019;Kim, Hermundstad, Romani, Abbott, & Jayaraman, 2019).…”
Section: Discussionsupporting
confidence: 76%
“…Similar to these beetles (el Jundi et al, 2015b), we know that the central complex acts as an internal compass for the butterfly’s migration (Heinze and Reppert, 2011; el Jundi et al, 2014). Thus, this brain region likely plays a major role in the integration of sun and terrestrial compass information as it provides the neuronal substrate that allows a flexible combination of different cues in the insect’s compass (Fisher et al, 2019; Kim et al, 2019; Seelig and Jayaraman, 2015). The results here show that non-migrating monarch butterflies can keep constant headings with respect to a visual scene based on skylight and terrestrial cues, similar to what migrating butterflies do during their annual journey.…”
Section: Discussionmentioning
confidence: 99%
“…Integration of multiple visual cues does not require a certain context (migration or homing) but is a common strategy of insects to keep track of their heading with respect to their environment, irrespective of their behavioral state. Neurobiological studies in flying fruit flies showed that the insect’s internal compass encodes the entire visual scene in a highly flexible manner (Fisher et al, 2019; Kim et al, 2019). This highly dynamic coding of visual cues allows an insect to constantly integrate multiple cues, such as a panoramic scenery, in its compass and to set it in relation to the sun’s position.…”
Section: Introductionmentioning
confidence: 99%
“…More recent imaging studies and recordings from ring and EP-G neurons in the EB have uncovered the likely mechanism that underlies how the bump of activity within the EB becomes linked to the direction of a visual cue (Fisher et al, 2019;Kim et al, 2019). Individual ring cells in the EB respond to visual cues in a specific retinal position.…”
Section: Discussionmentioning
confidence: 99%
“…The turn amplitudes that are likely to be mediated by known CX circuitry are of several kinds. Turns that place a visual stimulus in its expected position, like turns towards and away from the bar, can be understood within the framework of the previous paragraph (Fisher et al, 2019;Kim et al, 2019). Turns in the direction of the home vector are also likely to involve the CX, in this case, interactions between the fan-shaped body, the protocerebral bridge and the EB (Neuser et al 2008;Stone et al, 2017;Honkanen et al 2019, Le Moël et al, 2019.…”
Section: Discussionmentioning
confidence: 99%